Legal Drafting and Editing in Academic Studies. (5th December 2015) - Stepanova, Valentina
Abstract: The article looks at legal drafting and editing as the focus of academic studies. The interest to this topic is determined by practical needs in a globalizing world where English is the language of business communication. Other reasons stem from the public demand for more understandable and clear legal instruments, legislative and policy initiatives and innovations in software and printing technologies. The article outlines the key aspects of legal drafting and editing/revising based on the works of Russian and Western scholars. It examines linguistic and non-linguistic properties of the legal instruments (on the material of corporate documents) contributing to their clarity and readability and, as a practical part of the research, analyses the most common errors in translating the articles of association from Russian into English.